Grass and grass-legume mixes for irrigated pasture using organic production methods - Booher, Matthew R., author; Brummer, Joe E., advisor; Davis, Jessica G., committee member; Meiman, Paul J., committee member (Colorado State University. Libraries, 2010)
Species selection and fertility management are two of the greatest challenges facing producers of organic pasture. The objectives of this study were to: 1. Identify irrigated grass and grass-legume mixtures that possess the productivity, durability, and forage quality to meet the needs of organic dairies in the western US. 2. Evaluate the use of legumes and compost as nutrient sources for pastures being managed in accordance with organic protocols. Research was conducted for two years at the Agricultural Research, Development, and Education Center located about 4 km south of Wellington, CO. Four grass mixes: tall fescue (TF), hybrid wheatgrass-tall fescue-hybrid brome (HWG-TF-HB), orchardgrass-meadow brome-smooth brome (OG-MB-SB), and orchardgrass-meadow brome-Kentucky bluegrass (OG-MB-KB), were established in fall 2007. In 2008, plots received either a compost treatment of 22.4 Mg ha-1, or were part of a control set that received no compost. Plots were harvested six times in 2008 to simulate rotational grazing, and dry matter (DM) yield, crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF) were determined at each cutting. Fertility (compost) had no effect in 2008. Total DM yield of TF (10,864 kg ha ha-1) was higher than OG-MB-SB (9,241 kg ha ha-1) and OG-MB-KB (8,079 kg ha ha-1). Dry matter yield of TF in late-September was 120% higher than the other grass mixes. In general, forage contained higher CP and lower NDF and ADF as the season progressed, resulting in increased forage quality over time. Averaged across cutting date, CP of TF (19.8 %) was 9% lower than the other grass mixes; however, CP remained adequate to meet most ruminant needs for all grass mixes at all cutting dates. In 2009, the 22.4 Mg ha ha-1 compost fertility treatment was divided to include an 11.2 Mg ha ha-1 treatment and a 0 Mg ha ha-1 control, in an effort to observe nitrogen mineralization from previous compost applications. Also in 2009, alfalfa, birdsfoot trefoil, sainfoin, and white clover were interseeded into the 2008 control plots to observe legume effects on yield and forage quality. Yield and quality data were taken for five cuttings in 2009. As a result of a low level of nitrogen in the compost, fertility had no effect on yield or quality in 2009. Total DM yield in 2009 averaged about 45% less than in 2008. Total DM yields of TF and HWG-TF-HB averaged 23% higher than the other grass mixes. Crude protein content averaged about 6 percentage points lower in 2009 than in 2008, most likely due to nitrogen deficiency. Similar to 2008, TF was lower in CP than the other grass mixes. In general, forage quality improved over the season. On average, TF (56.2 %) and HWG-TF-HB (56.9 %) had a 4% higher NDF content than the other grasses, while all grass mixes had a similar average ADF content of around 32%. Because legumes did not significantly contribute to harvested yield until cuttings 4 and 5 in 2009, cuttings 1-3 were not included in analyses of the legume treatments. The alfalfa treatment had 25% higher DM yield than the other legume treatments, due to the greater presence of alfalfa in the plots. Mix and cutting date affected CP content of the sward within the legume treatments. Similar to the results observed in the compost treatments, tall fescue had lower average CP content than the other grass mixes within the legume treatment, while OG-MB-SB averaged higher than the other grass mixes. Cutting effects for the legume treatment were similar (decreasing CP) to the compost treatment for the period analyzed (cuttings 4 and 5). NDF was affected by legume species, probably due to the greater abundance of alfalfa in the plots. The OG-MB based mixes in the legume treatments averaged 6% lower in NDF content than the other grass mixes. The management implications of this study vary based on the relative importance of pasture in an animal's diet. Tall fescue tended to yield higher than the other grass mixes in the study, but had lower CP content. While this difference may be statistically significant, levels of CP for all grasses (including TF) were adequate for most animal needs. In addition, digestible fiber content was highest in mixes containing TF, making this grass an excellent choice for producers desiring high yields, durability, and overall good quality. Conversely, the OG-MB-SB mix, while showing a moderate yield and CP content, had a higher proportion of indigestible fiber than all other mixes. This appears to be a product of the smooth brome component in the mix, and presents a case for avoiding this species if high digestibility is desired. In general, forage quality of all grass mixes improved over the growing season, peaking in late summer and fall. This study found that the addition of legumes to grass-based pasture is an excellent tool for increasing forage quality, especially crude protein content. Additionally, nitrogen management (i.e. compost testing) is vital to forage productivity and quality when using organic fertility sources.
Department Head: Gary Peterson.